Man United with God (Theodosius Hagiography of St. Peter Koriski, interpretation) - Kostić, Dragomir J. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The story about a man who insulate himself in the desert, he chose suffering and starvation, and who won demons even outside himself as well as inside himself, devoting only a single goal, love towards God. He was the one who in his entire life taking care only about how to reach to God, who is subordinate to God, who only wanted God, longed only for God! He is losing its character, stood in front the face of God; losing himself, he found Him. "Well and good saponification to myself and listeners useful learning”... it is this hagiography according to its author. It differs significantly from the previous hagiography of this writer, Hagiography of Saint Sava. In This literary work was highlighted the presence of the author. He writes about the saint’s life and asceticism, but also writes about how, in what way and after whose speech is created hagiography about Peter Koriski and some of his characteristics (qualities).